2020
DOI: 10.3390/antiox9090779
|View full text |Cite
|
Sign up to set email alerts
|

The BACH1/Nrf2 Axis in Brain in Down Syndrome and Transition to Alzheimer Disease-Like Neuropathology and Dementia

Abstract: Down syndrome (DS) is the most common genetic cause of intellectual disability that is associated with an increased risk to develop early-onset Alzheimer-like dementia (AD). The brain neuropathological features include alteration of redox homeostasis, mitochondrial deficits, inflammation, accumulation of both amyloid beta-peptide oligomers and senile plaques, as well as aggregated hyperphosphorylated tau protein-containing neurofibrillary tangles, among others. It is worth mentioning that some of the triplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 90 publications
0
24
1
Order By: Relevance
“…An increasing number of studies have recently shown that increased OS is an early pathological characteristic of the DS brain and is involved in the onset and progression of AD due to the deregulation of gene/protein expression associated with HSA21 [ 71 , 72 , 73 , 74 ]. OS indicates a condition where pro-oxidant species overwhelm the cellular antioxidant defense system, by an increase of ROS production and/or by a decrease in the antioxidant response [ 17 ].…”
Section: Stress Responses In Down Syndrome Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies have recently shown that increased OS is an early pathological characteristic of the DS brain and is involved in the onset and progression of AD due to the deregulation of gene/protein expression associated with HSA21 [ 71 , 72 , 73 , 74 ]. OS indicates a condition where pro-oxidant species overwhelm the cellular antioxidant defense system, by an increase of ROS production and/or by a decrease in the antioxidant response [ 17 ].…”
Section: Stress Responses In Down Syndrome Brainmentioning
confidence: 99%
“…Noteworthy, the mechanisms responsible for the increase of OS levels in DS may be searched by mapping HSA21, where a number of genes, directly or indirectly, promote free radical production and alter the redox homeostasis of brain cells ( Figure 1 ). Among these, SOD1, APP, carbonyl reductase, and the transcription factor BTB and CNC homology 1 (Bach1) have been recognized as ROS inducers [ 73 , 74 ]. SOD1 catalyzes the dismutation of O 2 •− to O 2 and H 2 O 2 , the latter in turn is neutralized by catalase (CAT) and by glutathione peroxidase (GPX) to water [ 96 ].…”
Section: Stress Responses In Down Syndrome Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to neuroinflammation, increased free radical levels and oxidative stress disturb beta-amyloid clearance, which in turn induces cerebral amyloidosis ( Tönnies and Trushina, 2017 ). Neuronal oxidative stress also alters mitochondrial metabolism, enhances neuroinflammation, and increases apoptosis, causing neuronal loss and hyperphosphorylation of Tau proteins ( Butterfield and Boyd-Kimball, 2018 ; Perluigi et al, 2020 ).…”
Section: Stress Depression and Alzheimer's Disease: A Bio-continuummentioning
confidence: 99%
“…Moreover, triplication of the S100B and APP genes upregulates the expression of IL-1B protein, which increases neuroinflammation ( Wilcock and Griffin, 2013 ). In terms of oxidative stress, patients with DS show higher oxidative stress levels because of alterations of the kynurenine metabolic pathway, decreased production of antioxidants, and triplication of the SOD1, RCAN1 and APP genes ( Gomez et al, 2020 ; Perluigi et al, 2020 ). Finally, patients with DS also show (i) increased tau hyperphosphorylation because of the triplication of the ETS2 and DYRK1A genes ( Gomez et al, 2020 ; Hartley et al, 2015 ), (ii) increased neuronal apoptosis caused by the coordinated action of SOD1, DYRK1A, and ETS2 ( Martínez-Cué and Rueda, 2020 ), (iii) increased mitochondrial dysfunction linked to the triplication of the S100B and SOD1 genes ( Dierssen et al, 2020 ), and (iv) altered endocytosis and synaptic trafficking because of triplication of the RCAN1 and SYNJ1 genes ( Gomez et al, 2020 ).…”
Section: The Impact Of Psychological Stress On Patients With Down Synmentioning
confidence: 99%